Statistical Analysis of Employment and Health Impacts on Demographic Trends in the Kakheti Region of Georgia - Dokhturishvili, Nino; Abesadze, Nino (Dr. Viktor Koval, 2025)
Introduction. The demographic situation in Georgia and its regions, particularly in Kakheti, remains tense and manifests in a decrease in the birth rate, a negative natural increase, a decrease in marriage and an increase in divorce, and high migration rates. In this regard, there is a need for an in-depth analysis of these factors that reflect serious demographic challenges, to predict future changes in the population structure. Understanding these processes can help develop effective strategies to improve the demographic situation and create conditions for sustainable socioeconomic development in the region. Aim and tasks. The study aims to conduct a comprehensive analysis of the demographic expectations and existing variations within Kakheti region of Georgia. Results. The demographic situation in Kakheti region of Georgia was analysed based on the results of a survey conducted monthly from 2023 to 2024 among residents of the region aged 15 to 50 years. The empirical analysis showed that economic conditions and the health of one of the spouses were the main reasons for the decline in the birth rate. For most respondents, the primary source of income was employment in the public sector and private business, with a significant portion of respondents (72.7%) assessing their financial situation as satisfactory. Among the factors influencing health and life expectancy, the respondents highlighted economic well-being (22%) and environmental conditions (21.4%) as the most significant. Families with stable incomes prefer having two or three children, while low-income families are not prepared to have four or more children. The role of economic (income) and educational factors (education level) influencing the demographic attitudes of respondents was emphasised. Conclusions. There is an apparent discrepancy between the ideal and actual number of children in families. A balance between the desired and actual number of children is lacking n many families. There has been a change in the demographic behaviour of different generations. The main reasons for having fewer children than desired were economic conditions and the health of one of the spouses. For most respondents, the primary source of income was employment in the public sector and private businesses.